PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, LEVERAGE TERHADAP KONSERVATISME AKUNTANSI DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Yuniarsih, Nia; Permatasari, Anita (Universitas 17 Agustus 1945 Surabaya, 2021)
The principle of conservatism is the principle of prudence against an uncertain situation to avoid excessive optimism from management and company owners. Consequently, if there is a condition that is likely to cause loss, expense or debt, the loss, cost or debt must be recognized immediately. The variables used in this study include Institutional Ownership, Managerial Ownership, Leverage, Profitability and Accounting Conservatism. This research is a quantitative research conducted on manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2018. The results of this study are institutional ownership has an effect on accounting conservatism; Managerial ownership affects accounting conservatism, leverage affects accounting conservatism, profitability affects accounting conservatism, and profitability moderates the variables of institutional ownership, managerial ownership, and leverage on accounting conservatism.